Comparison of Strength, Consistency, and Speed of COR-KNOT versus Manually Hand-Tied Knots in an Ex Vivo Minimally Invasive Model. Issue 2 (March 2014) - Lee, Candice Y.; Sauer, Jude S.; Gorea, Heather R.; Martellaro, Angelo J.; Knight, Peter A.
Objective: This study compared the strength, consistency, and speed of prosthetic attachment sutures secured with automated fasteners with those of manual knots using an ex vivo porcine mitral valve annuloplasty model. A novel miniature pressure transducer system was developed to quantify pressures between sutured prosthetic rings and underlying cardiac tissue. Methods: Sixteen mitral annuloplasty rings were sewn into ex vivo pig hearts. Eight rings were secured with the COR-KNOT device; and eight rings, with hand-tied knots using a knot pusher. A cardiac surgeon and a surgery resident each completed four manually tied rings and four COR-KNOT rings via a thoracotomy trainer. The total time to knot and cut each ring's sutures was recorded. Suture attachment pressures were measured within (intrasuture) and between (extrasuture) each suture loop using a 0.5 × 2.0-mm microtransducer probe system. Results: The suture holding pressures for the COR-KNOT fasteners were significantly greater than for the manually tied knots (median, 1008.9 vs 415.8 mm Hg, P < 0.001). All automated fasteners measured greater than 500 mm Hg, whereas 56% of the hand-tied knots were less than 500 mm Hg, and 14% were less than 75 mm Hg. There was less variation in attachment pressures for the COR-KNOT fasteners than for the hand-tied knots (SD, 401.6 vs 499.3 mm Hg, P = 0.04). Significant time savings occurred with the use of the COR-KNOT compared with manual tying (12.4 vs 71.1 seconds perknot, P = 0.001). Conclusions: The novel microtransducer technology provided an innovative means of evaluating cardiac prosthetic anchoring sutures. In this model, mitral annuloplasty ring sutures secured with the COR-KNOT device were stronger, more consistent, and faster than with manually tied knots.